Cobalt‐Encapsulated Nitrogen‐Doped Carbon Nanotube Arrays for Flexible Zinc–Air Batteries. Issue 1 (11th November 2019) - Liu, Lina; Wang, Yue; Yan, Feng; Zhu, Chunling; Geng, Bo; Chen, Yujin; Chou, Shu‐lei
Abstract: With the current rapid growth of commercial applications for flexible and wearable optoelectronic devices, flexible power sources are very much in demand. Herein, a facile strategy to grow cobalt nanoparticles encapsulated in nitrogen‐doped carbon nanotube arrays on flexible carbon fiber cloth as self‐supported electrodes for high‐performance flexible zinc–air batteries is developed. Benefiting from high electrical conductivity and multiple active sites as well as free polymer binder, the self‐supported electrode exhibits excellent electrocatalytic activity. The maximum power density of a zinc–air battery using the self‐supported electrode as air cathode is higher than that of the zinc–air battery with Pt/C+IrO2 as air electrode. Furthermore, the zinc–air battery can be stably operated under external stress without obvious loss of the electrochemical performance. This work opens up a new pathway for the rational design of flexible electrodes for high‐performance flexible power sources. Abstract : Flexible zinc–air batteries assembled with cobalt nanoparticles encapsulated in nitrogen‐doped carbon nanotube arrays show excellent electrochemical performance that can power a toy car and light up a light‐emitting diode lamp under extreme bending conditions.